2016
DOI: 10.1159/000438642
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Protects Thymic Epithelial Cells from Mitomycin C-Mediated Apoptosis In Vitro via Trx2-NF-κB-Bcl-2/Bax Axis

Abstract: Background/Aims: Age-associated and stress-induced involution of the thymus is accompanied by reduced numbers of thymic epithelial cells (TECs) and severe reduction in peripheral T cell repertoire specificities. These events seriously affect immune function, but the mechanisms involved are unclear. Our preliminary findings showed that doxycycline (Dox) could drive the proliferation of a TEC line (MTEC1 cells) partially via the MAPK signaling pathway. Dox can also up-regulate IL-6 and GM-CSF expression via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Stress is able to disrupt homeostasis of the immune system, and various stressful conditions cause acute thymic involution, including emotional distress, malnutrition and pregnancy ( 56 , 57 ). Furthermore, numerous processes can trigger thymic involution during pathological conditions, such as bacterial and viral infections, inflammation, disease, clinical cancer treatment and preparative regimens for bone marrow transplants ( 58 ), as presented in Fig.…”
Section: Regulation Of Molecular Mechanisms In Stress-mediated Thymicmentioning
confidence: 99%
“…Stress is able to disrupt homeostasis of the immune system, and various stressful conditions cause acute thymic involution, including emotional distress, malnutrition and pregnancy ( 56 , 57 ). Furthermore, numerous processes can trigger thymic involution during pathological conditions, such as bacterial and viral infections, inflammation, disease, clinical cancer treatment and preparative regimens for bone marrow transplants ( 58 ), as presented in Fig.…”
Section: Regulation Of Molecular Mechanisms In Stress-mediated Thymicmentioning
confidence: 99%
“…Because ATI has been confirmed to be plastic in nature, it can be therapeutically reversed or halted (Wang et al 2016). Figure 5b illustrates the potential mechanisms underlying the therapeutic treatment of ATI in vitro (Wang et al 2016).…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%
“…Other alterations include, but are not limited to, changes in the thymic epithelial cells (TECs), cortico-medullary ratio and apoptosis rates in the affected thymic tissues (Elmore 2006). Growing evidence suggests that ATI is plastic in nature and thus can be therapeutically reversed or halted (Wang et al 2016). For this reason, we also highlight recently discovered mechanistic and therapeutic tools (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported that IL-1β and TNF-α induced the nuclear translocation of NF-κB [10][11][12][13][14]. en, NF-κB activated the downstream Bcl-2 family proteins to regulate apoptosis [15,16]. Bcl-2 and Bax are both important members in the Bcl-2 family, which involved in the mechanism of apoptotic cell death [17].…”
Section: Introductionmentioning
confidence: 99%